Enterprise Restructuring and Transition : Evidence From the Former Yugoslav Republic of Macedonia - Zalduendo, Juan (IMF Working Papers; Working Paper, 2003)
This paper reviews developments in corporate performance in the FYR Macedonia during the 1990s. The paper finds substantial differences in performance between surviving old firms and nimbler new ones. The paper reviews factors that facilitated restructuring among surviving firms, and concludes that private sector ownership, hard budget constraints, and market-based economic institutions have served to strengthen corporate performance. The paper also shows that the predominance of insider privatization and the resulting low ownership concentration is one of the reasons for the poor performance of surviving firms.